The Role of Social Media Algorithms in Improving Islamic Financial Literacy: A Systematic Literature Review - Hafifuddin Hafifuddin; Ujang Sumarwan; Popy Novita Pasaribu (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Indonesia is one of the countries with resident Muslim the largest in the world. According to 2025 data there are as many as 249.82 million soul residents who are Muslim and this equivalent with 87.14% of the total number Indonesian population with social media usage in 2026 will be 180 million people, which is equivalent to with 62.9% of the total population . With amount social media users as big as That so potential use of social media For development industry finance in Indonesia is very big and includes How increase literacy public to Islamic finance . Social media algorithms is technique or the process used social media companies For filter and analyze the displayed data to users in accordance with interactions , preferences , and information other with objective For increase interaction and engagement users with the platform. The main goal from study This is understand How method Work social media algorithms in literacy Islamic finance and what only what is necessary be noticed so that you can impact maximum to literacy Islamic finance Method: This study employed the systematic literature review approach in exploring the link that connects social media algorithms and Islamic Financial Literacy. The systematic literature review approach was carried out based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were collected from several academic databases, including Scopus, ScienceDirect, and Google Scholar, using keywords such as algorithm, social media, and Islamic financial literacy . Results: In context literacy finance , algorithms ( such as on YouTube or TikTok platforms) can paired with content educative For reach specific audience . With​ phenomenon Filter Bubble & Echo Chamber Phenomenon algorithm Can strengthen narrative finance Islam in a way more Exclusive . Priority on Content Sensational can also be done Because algorithm often prioritize​ triggering content​ response emotional strong or which is of a nature sensational in order to increase engagement. However so also necessary made into attention about distribution misinformation. Without strict supervision , algorithm​ can speed up distribution information finances that are not accurate or investment illegal wrapped in with religious narrative Conclusion: The role of social media algorithms in increase literacy Islamic finance relies heavily on design ethical algorithms , transparency​ system recommendations , as well as ability authority religious and academic For produce content quality competitive height in the digital space . Without accompanied by with literacy powerful algorithmic​ from side users For filter information in a way critical , algorithm risky become tool manipulation eroding discourse​ authority science traditional and worsening inequality knowledge religious